ABOUT RESILIENCE AND THE WELL-BEING OF STUDENTS IN A PANDEMIC CONTEXT - Gabriela MOTOI; Alexandrina Mihaela POPESCU (Universitaria Publishing House, Craiova, 2021)
In the context of the pandemic caused by SARS-CoV-2 which has lasted for almost 2 years and which has determined the transition of universities to online education, we consider it important to address the issue of the resilience and wellbeing of the students. The well-being and excellence of the students are interlacing and starting from this reality it makes well-being very important. Universities are not only a place for the students to learn, they should be a place where well-being is a priority, giving students the opportunity to participate in activities that are important to them, where they can experience positive emotional states, can be valued, encouraged to gain success, to experience feelings of belonging to the academic community. Our study aims to identify the well-being of the students during the pandemic and the need to develop and implement certain academic resilience programs. Because in the specialised literature the concept of well-being is a polysemantic one, we will approach well-being considering the following components: mental state, emotional state, physical health and social interactions.